The autobiography of Eleanor Roosevelt. - Roosevelt, Eleanor (New York Da Capo Press, 1992)
The long and eventful life of Eleanor Roosevelt (1884?1962) was full of rich experiences and courageous actions. The niece of Theodore Roosevelt, she married a distant relative and Columbia University law student named Franklin Delano Roosevelt; he gradually ascended throughout the world of New York politics to reach the U.S. presidency in 1932. Throughout his three terms, Eleanor Roosevelt was not only intimately involved in FDR?s personal and political life, but led women?s organizations and youth movements and fought for consumer welfare, civil rights, and improved housing. During World War II she traveled with her husband to meet leaders of many powerful nations; after his death in 1945 she worked as a UN delegate, chairman of the Commission on Human Rights
Originally published: New York : Harper & Brothers, 1961.
Keywords: Roosevelt, Eleanor, 1884-1962.